2017
DOI: 10.1186/s40659-017-0124-9
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 inhibition suppresses cell growth, migration and invasion of salivary adenoid cystic carcinoma

Abstract: BackgroundBromodomain-containing protein 4 (BRD4) inhibition is a new therapeutic strategy for many malignancies. In this study, we aimed to explore the effect of BRD4 inhibition by JQ1 on in vitro cell growth, migration and invasion of salivary adenoid cystic carcinoma (SACC).MethodsThe human normal epithelial cells and SACC cells (ACC-LM and ACC-83) were treated with JQ1 at concentrations of 0, 0.1, 0.5 or 1 μM. Cell Counting Kit-8 (CCK-8) assay was performed to evaluate cell proliferation. Cell apoptosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…Consistent with a prominent effect of BET inhibition on blocking EndoMT observed herein 11 , JQ1 has been reported to mitigate EMT in carcinomic 17,19 and pulmonary 20 epithelial cells, although without identification of the specific BET family members or BDs involved. Interestingly, a very recent report identified BRD2 as the key regulator of EMT with BRD3 and BRD4 playing an opposite role 21 .…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with a prominent effect of BET inhibition on blocking EndoMT observed herein 11 , JQ1 has been reported to mitigate EMT in carcinomic 17,19 and pulmonary 20 epithelial cells, although without identification of the specific BET family members or BDs involved. Interestingly, a very recent report identified BRD2 as the key regulator of EMT with BRD3 and BRD4 playing an opposite role 21 .…”
Section: Discussionsupporting
confidence: 63%
“…It can promote cell proliferation, cell-cycle progression, survival and apoptosis resistance [46]. Several of these genes have been indentified, including cyclin D1, Bcl-2 and c-Myc [38,[47][48][49][50][51]. Our results show that BRD4 silencing by targeted shRNAs led to c-Myc downregulation in 786-O cells.…”
Section: Discussionsupporting
confidence: 48%
“…Melatonin has been reported to inhibit NP cell proliferation and matrix remodeling, while ERRFI1 has been found to inhibit proliferation and alleviate inflammation of NP cells (Guo et al, 2019; Li et al, 2017). Numerous reports have revealed that BRD4 promotes cell proliferation in gastric cancer and cutaneous T‐cell lymphoma (Ba et al, 2018; Dong, Hu, Chen, Hu, & Chen, 2018; Kamijo et al, 2017; Wang et al, 2017). Herein, the CCK‐8 and flow cytometry results revealed that JQ1 inhibited proliferation by inducing cell cycle arrest in G0/G1 phase.…”
Section: Discussionmentioning
confidence: 99%